Psychospiritual care: a concept analysis - Khotibul Umam; Ira Suarilah; Eva Belingon Felipe-Dimog; Ah. Yusuf; Imam Susilo (PAGEPress Publications, 2024)
Psychospiritual care has taken many forms and approaches. In the clinical setting, the meaning, variations, and inconsistencies in the delivery of psychospiritual and its related terms persist. The purpose of the study is to identify the meaning and attributes of psychospiritual care and enhance collaborative practice by presenting a concept analysis. This review used Walker and Avant's eight-step approach to concept analysis. Psychospiritual is a broad, dynamic, and unique concept that integrates psychological and spiritual methods. In this analysis, the defining attributes of psychospiritual care are intuitive self-awareness, therapeutic use of psychological and spiritual perspective, and cultivation of psychological and spiritual environment. Providing psychospiritual care promotes positive consequences, such as therapeutic effects for patients and promoting psychospiritual awareness among psychospiritual interventionists. A comprehensive definition of psychospiritual care has been developed. The findings contribute to science by creating a platform for developing practice standards, research, and theory. Implementing psychospiritual care may improve overall occupational health and well-being, thereby improving patient care delivery.